Investigation of cell cytotoxic activity and molecular mechanism of 5β,19-epoxycucurbita-6,23(E)-diene-3β,19(R),25-triol isolated from Momordica charantia on hepatoma cells - Mei-Kang Yuan; Ju-Wen Kao; Wen-Tung Wu; Chiy-Rong Chen; Chi-I Chang; Yu-Jen Wu (Taylor & Francis Group, 2022)
Context Momordica charantia L. (Cucurbitaceae), known as bitter melon, is an edible fruit cultivated in the tropics. In this study, an active compound, 5β,19-epoxycucurbita-6,23(E)-diene-3β,19(R),25-triol (ECDT), isolated from M. charantia was investigated in regard to its cytotoxic effect on human hepatocellular carcinoma (HCC) cells.Objective To examine the mechanisms of ECDT-induced apoptosis in HCC cells.Materials and methods The inhibitive activity of ECDT on HA22T HCC cells was examined by MTT assay, colony formation assay, wound healing assay, TUNEL/DAPI staining, annexin V-fluorescein isothiocyanate/propidium iodide (PI) staining and JC-1 dye. HA22T cells were treated with ECDT (5, 10, 15, 20 and 25 μM) for 24 h, and the molecular mechanism of cells apoptosis was examined by Western blot. Cells treated with vehicle DMSO were used as the negative control.Results ECDT inhibited the cell proliferation of HA22T cells in a dose-dependent manner. Flow cytometry showed that ECDT treatment at 10-20 μM increased early apoptosis by 10-14% and late apoptosis by 2-5%. Western blot revealed that ECDT treatment activated the mitochondrial-dependent apoptotic pathway, and ECDT-induced apoptosis was mediated by the caspase signalling pathway and activation of JNK and p38MAPK. Pre-treatment of cells with MAPK inhibitors (SB203580 or SP600125) reversed the ECDT-induced cell death, which further supported the involvement of the p38MAPK and JNK pathways.Discussion and conclusions Our results indicated that ECDT can induce apoptosis through the p38MAPK and JNK pathways in HA22T cells. The findings suggested that ECDT has a valuable anticancer property with the potential to be developed as a new chemotherapeutic agent for the treatment of HCC.